One-minute synthesis via electroless reduction of amorphous phosphorus-doped graphene for oxygen reduction reaction - Poon, Kee Chun (2022)
This study reports a simple one-step electroless reduction synthesis of amorphous phosphorus-doped graphene (RGO-P). In just 1 min, RGO-P was synthesized under ambient conditions via a one-step simultaneous reduction and doping of graphene oxide (GO). RGO-P was found to be amorphous with P being essential for the formation of the amorphous structure. RGO-P exhibited enhanced electrocatalytic performance for the oxygen reduction reaction (ORR). The amorphous RGO-P demonstrated superior specific activity and durability compared to crystalline reduced graphene oxide (RGO). Annealing results showed that the amorphous nature of RGO-P was the key factor in its high catalytic activity.